Renal Handling of Sclerostin in Response to Acute Glomerular Filtration Decline - Kakareko, K.; Rydzewska-Rosolowska, A.; Brzosko, S.; Gozdzikiewicz-Lapinska, J.; Koc-Zorawska, E.; Samocik, P.; Kozlowski, R.; Mysliwiec, M.; Naumnik, B.; Hryszko, T. (Hormone and Metabolic Research, 2016)
Deterioration of glomerular filtration rate (GFR) is associated with alterations of bone metabolism. It translates clinically to bone fragility and increased fractures rate among patients with impaired GFR. Recently, sclerostin (SCL) gained much attention as an important factor in pathogenesis of mineral and bone disturbances in patients with renal diseases. There is no data about SCL behaviour in patients with acute GFR decline. The aim of this study was to evaluate the renal handling of SCL. This is a prospective, single-centre observational study in patients undergoing nephrectomy due to urological indications. Serum and urinary SCL levels were measured prior and after nephrectomy. 25 patients were enrolled. After surgery, eGFR significantly declined (from 87.4±19.7 to 67.7±25.7 ml/min/1.73 m2, p<0.0001). Nephrectomy caused more than 20 times higher renal fractional excretion of SCL [0.15 (interquartile range, IQR 0.09–0.40) vs. 2.78 (IQR 1.51–4.02)%, p<0.001], while its serum level remained intact [0.69 (IQR 0.57–0.90 vs. 0.65 (IQR 0.53–0.88) ng/ml, p=0.4]. The magnitude of eGFR reduction was associated inversely with change in urinary SCL fractional excretion (r=−0.6, p=0.001) and with alteration in serum SCL level (r=−0.5, p=0.01). Our results suggest that increased serum SCL concentrations at moderately reduced GFR are not due to diminished renal clearance. At more severely decreased GFR, elevated SCL concentration results from both increased production and reduced renal elimination.
Keywords: acute GFR decline; sclerostin; nephrectomy; parathyroid hormone